Manajemen Sarana dan Prasarana di Sekolah Menengah Atas Negeri 1 Kutorejo - Fiki Amaliatul Ilmi; Farida Ulvi Na'imah (Journal of Social, Educational and Religious Studies, 2025)
Educational facilities and infrastructure are essential resources that support the overall learning process in schools. Difficulties in managing them become more significant when management systems and procedures are unclear, or when the willingness and ability of managers are inadequate. The primary focus of this study is to examine the application and implementation of facilities and infrastructure management functions at State Senior High School 1 Kutorejo. The purpose of this research is to analyze the process of facilities and infrastructure management within the school. This study employs a qualitative method with a descriptive approach and was conducted at State Senior High School 1 Kutorejo using observation, interviews, and documentation techniques for data collection. The research findings indicate that implementation of facilities and infrastructure management follows several structured stages. The first stage is planning, which is conducted through coordination meetings involving the school principal, vice principal for facilities and infrastructure, teachers, and administrative staff. The second stage is procurement, carried out based on planning results, needs analysis, and consideration of budget availability. The third stage is distribution, ensuring that items are evenly allocated throughout the school. The fourth stage is storage, in which items are kept in proper warehouses under direct supervision. The fifth stage involves maintenance, performed regularly to ensure that facilities remain in good condition. The sixth stage is inventory, conducted systematically to record the quantity and condition of items accurately. The final stage is disposal, intended to remove unused or severely damaged items. However, the disposal process at the school occurs infrequently, resulting in difficulties and inefficiencies in inventory management.